Ocean literacy and how serious games can play a part: the case of the jellyfish and the microplastics governance game MoreGoJelly! - Rachel Tiller; Ina Helene Ahlquist; Håvard Almås; Emily Cowan; Dorothy Dankel; Magnus Hakvåg (Cambridge Prisms: Plastics)
Serious games are a method that can be used to reach the public on complex topics related to the ocean. Although games used for learning generally, and ocean literacy specifically, have developed gradually since the 1970s, it was not until the popularization of digital games, around the turn of the millennium, that serious games rose to prominence in academia. Since then, vast amounts of serious games research have been published each year – chiefly on digital games, but also increasingly on hybrid and analogue games. In this article, we present results from a series of serious games that were played in three geographical regions in Norway with future-generation stakeholders and tie this to ocean literacy. We report on the potential benefits of serious games for learning and motivation based on these results. The games were played within the context of the United Nations Decade of Ocean Science, the sustainable development goals and multilevel governance, with a special focus on microplastic pollution and jellyfish blooms. We argue that using serious games can be beneficial not just for outreach but also as a tool for unintrusive collection of qualitative data in the form of narratives from transcriptions post-gaming session and contribute to ocean literacy.